2006
DOI: 10.1063/1.2260821
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent evolution of the local electronic structure of atmospheric plasma treated carbon nanotubes: Near edge x-ray absorption fine structure study

Abstract: Near edge x-ray absorption fine structure ͑NEXAFS͒ spectroscopy has been employed to obtain the temperature dependent evolution of the electronic structure of acid treated carbon nanotubes, which were further modified by dielectric barrier discharge plasma processing in an ammonia atmosphere. The NEXAFS studies were performed from room temperature up to 900°C. The presence of oxygen and nitrogen containing functional groups was observed in C K edge, N K edge, and O K edge NEXAFS spectra of the multiwalled carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…Second, nitrogen functional groups doped in the carbon matrix are believed to be active for the ORR. The transition metals do not take part in the ORR, but the addition of transition metal in the catalyst synthesis facilitates the incorporation of nitrogen into the carbon matrix, which can increase the ORR active site density on the catalysts [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, nitrogen functional groups doped in the carbon matrix are believed to be active for the ORR. The transition metals do not take part in the ORR, but the addition of transition metal in the catalyst synthesis facilitates the incorporation of nitrogen into the carbon matrix, which can increase the ORR active site density on the catalysts [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that a heat treatment induce to the formation of more stable nitrogen functional groups [27,28]. Stanczyk et al [28] and Pel et al [29] showed that pyrrolic structures are transformed into pyridinic structures and vice versa via dynamic surface rearrangements during low temperature treatments.…”
Section: Introductionmentioning
confidence: 95%
“…NCNTs were also formed by dielectric barrier discharge plasma processing of acid treated CNTs in an NH 3 atmosphere [256]. The exposure of SWCNTs to microwave-generated N 2 plasma [257] was found to lead to SWNCNTs.…”
Section: N-containing Gas Plasma Treatment Of Cntsmentioning
confidence: 99%
“…CNTs functionalized with nitrogen nanocomposites can accelerate the cure and promote the wrapping of polymer molecules on them, which can act as a protective layer to prevent reagglomeration of dispersed CNTs . However, the use of plasma as a tool to insert nitrogen into CNTs still presents some difficulties, such as the low nitrogen molecule dissociation rate , the easy recombination of the nitrogen atoms , and the high instability of the nitrogenous groups . These difficulties are highlighted at Abrar et al work.…”
Section: Introductionmentioning
confidence: 99%